Influence of structural disorder on magnetic and transport properties of (La₀.₇Sr₀.₃)₀.₅(Pr₀.₆₅Ca₀.₃₅)₀.₅MnO₃ films - Prokhorov, V.G.; Flis, V.S.; Kaminsky, G.G.; Lee, Y.P.; Park, J.S.; Svetchnikov, V.L. (Физика низких температур, 2005)
Magnetic and transport properties of (La₀.₇Sr₀.₃)₀.₅(Pr₀.₆₅Ca₀.₃₅)₀.₅MnO₃ films prepared by a
«co-deposition» utilizing the laser-ablation technique are investigated in a wide temperature
range. The film deposited at 300 °C has a nano-crystalline disordered structure and exhibits a paramagnetic
temperature dependence of the magnetization with a narrow peak (ΔT ≃ 10 K) at
TG ≃ 45 K, which can be interpreted as a paramagnetic → superparamagnetic transition.
A short-term annealing of the as-deposited film at 750 °C leads to the formation of a high-textured
polycrystalline microstructure and to the appearance of ferromagnetic (FM) and metal—insulator
(MI) transitions at TC ≃ 240 K and TP ≃ 140 K, respectively. The observed discrepancy between
TP and TC values can be ascribed to a percolating nature of the MI transition, with an exponent of
5.3 for the percolating conductivity. The film deposited at Tsub ≃ 740 °C is composed of the lattice
strain-free and the lattice-strained crystallites with different lattice parameters and TC‘s, and is
consistently described in the framework of the Millis model [A.J. Millis, T. Darling, and A. Migliori,
J. Appl. Phys. 83, 1588 (1998)]. For a single-phase crystalline film obtain TC ≃ 270 K and
TP ≃ 260 K.